Comparative and analysis of evaluation of several direction of arrival estimation methods - Aya Ahkam Kamil; Marwa Moutaz Ismail; Bashar Sami Bashar (Universitas Ahmad Dahlan, 2021)
Modern-day, global, and clever array systems have several distinguished approaches with regard to a wireless device. In this paper, a comparative analysis has been carried out amongst nine (DOA) algorithms: Capon, MUSIC, Bartlett, Pisarenko, Linear prediction, Maximum entropies, and Min-norm, Root-MUSIC, and ESPRIT. in this paper reduces the number of antennas and snaps necessary to observe six targets without interference for several DOA estimation methods. After comparing and analyzing all the algorithms, it has been shown that the music algorithm is the best algorithm that reduces interference and detects the desired sources. MATLAB [R2019b] was used in the simulation process.